Untangling the Web: The Diverse Functions of the PIWI/piRNA Pathway - Mani, Sneha Ramesh (Mol Reprod Dev, 2013)
Small RNAs impact several cellular processes through gene regulation. Argonaute proteins bind small RNAs to form effector complexes that control transcriptional and post-transcriptional gene expression. PIWI proteins belong to the Argonaute protein family, and bind PIWI-interacting RNAs (piRNAs). They are highly abundant in the germline, but are also expressed in some somatic tissues. The PIWI/piRNA pathway has a role in transposon repression in Drosophila, which occurs both by epigenetic regulation and post-transcriptional degradation of transposon mRNAs. These functions are conserved, but clear differences in the extent and mechanism of transposon repression exist between species. Mutations in piwi genes lead to the upregulation of transposon mRNAs. It is hypothesized that this increased transposon mobilization leads to genomic instability and thus sterility, although no causal link has been established between transposon upregulation and genome instability. An alternative scenario could be that piwi mutations directly affect genomic instability, and thus lead to increased transposon expression. We propose that the PIWI/piRNA pathway controls genome stability in several ways: suppression of transposons, direct regulation of chromatin architecture and regulation of genes that control important biological processes related to genome stability. The PIWI/piRNA pathway also regulates at least some, if not many, protein-coding genes, which further lends support to the idea that piwi genes may have broader functions beyond transposon repression. An intriguing possibility is that the PIWI/piRNA pathway is using transposon sequences to coordinate the expression of large groups of genes to regulate cellular function.